HUBUNGAN FAKTOR DEMOGRAFI DAN POLA KONSUMSI DENGAN OBESITAS ABDOMINAL PADA WANITA USIA SUBUR DI INDONESIA - Mukhlidah Hanun Siregar; Ratu Ayu Dewi Sartika; Junengsih Junengsih; Kalinaki Hanifar (JURNAL KESEHATAN REPRODUKSI, 2024)
Background: There was an increase in the incidence of abdominal obesity among women of childbearing age in Indonesia. Impact on reproductive health such as sub infertility, irregular menstruation, and PCOS. Abdominal obesity also causes problems during pregnancy. Objective: This study aimed to analyze the association of demographics and patterns of food consumption with abdominal obesity in women of childbearing age in Indonesia. Method: This study used a cross-sectional design. The data used from Basic Health Research 2018. The total sample size was 29,888 respondents. Data analysis was performed by the Chi-Square test. Results: The result found the prevalence of abdominal obesity in women of childbearing age was 49.4%. Demographic factors associated with abdominal obesity were age, marital status, education level, and type of region. Patterns of food consumption associated were fatty foods/cholesterol/fried foods and burnt/grilled foods, with a risky frequency of more than 3 times per week. Conclusion: One of two women of childbearing age in Indonesia was abdominal obesity so we should make efforts to reduce this incidence with notice in demographic factors and dietary intake. Women of childbearing age need to avoid risky foods to maintain reproductive health and reduce the risk of cardiovascular disease, which increases with age.